"The explosion and the echo". Monograph by V.M. Kryukov and M.V. Kryukov "CER 1929" - Vladimir Datsyshen (Сравнительная политика, 2018)
Review of the monograph by Vassili M. Kryukov and Mikhail V. Kryukov, "CER 1929: Explosion and echo." This monograph is the third and final volume published in the framework of the research project "Documentary history of Soviet-Chinese relations (1917-1929)". The introduction gives a historiographical review of the Soviet-Chinese conflict of 1929 in Chinese Eastern railway, in which the authors identified 10 points of view (versions) of the events of 1929, and a review of sources. The text of the research, according to the problem-chronological principle, is divided into 12 chapters. The research is concluded with an "Epilogue" and a conclusion entitled "Some results of the research". The main advantage of the presented historical research is that the authors introduce into scientific circulation a huge array of documents from the collections of Russian, Chinese (Taiwan) and Western (UK, USA) archives. The disadvantage is that the authors did not address the materials stored in the regional archives of Russia and in various museums, they did not have access to the documents of the archives of the PRC. In the end, the monograph "KVZHD 1929" is the best today on the breadth of the source base and the depth of analysis of historical research. The release in Moscow of the book by V.M. Kriukov and M.V. Kriukov is a turning point in the development of the historiography of the Soviet-Chinese relations.